2013
DOI: 10.4103/1735-3327.113359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of allograft with doxycycline versus the allograft alone in the treatment of infrabony defects: A controlled clinical and radiographical study

Abstract: Background:Successful prevention and treatment of periodontal disease are contingent on effective control of periodontopathic microbiota based on the premise of periodontal disease being infectious disorders. An anti-microbial agent, i.e., doxycycline has been incorporated into the allograft to control infection and facilitate healing during and after periodontal therapy.Materials and Methods:Using a split-mouth design, 15 patients showing clinical evidence of almost identical bilateral infrabony defects requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Nearly 10 % of the almost 300 papers reviewed, stated or implied that no subgingival debridement was carried out in the test sites. For example, some authors reported that 'all patients underwent initial therapy, including oral hygiene instruction, scaling, and root planing everywhere except the study site' [27] or that 'in order to avoid pre-operative recession, teeth selected for GTR therapy did not receive subgingival instrumentation' [31], whilst other authors reported that only full-mouth supra-gingival scaling and oral hygiene instructions [32,33] or just oral hygiene instructions [34,35] were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 10 % of the almost 300 papers reviewed, stated or implied that no subgingival debridement was carried out in the test sites. For example, some authors reported that 'all patients underwent initial therapy, including oral hygiene instruction, scaling, and root planing everywhere except the study site' [27] or that 'in order to avoid pre-operative recession, teeth selected for GTR therapy did not receive subgingival instrumentation' [31], whilst other authors reported that only full-mouth supra-gingival scaling and oral hygiene instructions [32,33] or just oral hygiene instructions [34,35] were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Through their properties, these antibiotics have shown to enhance the bone-forming ability and to reduce bone resorption (Chaturvedi et al, 2008). Furthermore, studies showed that the local application of antibiotics with GTR or allograft promotes the attachment of fibroblasts to the root surface resulting in an increase to the collagen secretion and bone formation (Chang and Yamada, 2000;Kaur and Sikri, 2013).…”
Section: Antibiotics Agentsmentioning
confidence: 99%
“…In periodontal surgery, Doxycycline has been shown to improve wound healing, to increase osteogenic mediators, and to reduce collagenase (22). Recently, the benefits of doxycycline as an osteogenic agent was observed on the surface of bone implants (23), in healing of oral infrabony defects (24) and osteoclastogenesis downregulation in vitro (25).…”
Section: Introductionmentioning
confidence: 99%